Rancang Bangun Alat Monitoring dan Proteksi Kapasitor Bank Berbasis Internet of Things - Yayan Sopyan; Peby Wahyu Purnawan; Nifty Fath (MAESTRO, 2023)
ABSTRACT Capacitor bank is one of the electrical equipment that is needed in a building to improve the quality of the power factor so that the performance of other electrical equipment can be maintained properly. However, in the operation of capacitor banks, capacitors often overheat, resulting in explosions and then fires, as happened in a mall in the Depok area and the eastern part of Jakarta. Based on these problems, research was carried out to monitor and protect capacitor banks with Internet of Things (IoT) technology and the DS18B20 temperature sensor. The research only reached the prototype of the building's electrical network. The DS18B20 sensor attached to the capacitor body reads the temperature of the capacitor and the PZEM004T and SCT013 reads electrical parameters. The DS18B20 sensor functions as a temperature reader from the capacitor and the temperature reading results will be sent to the Arduino Mega which has been programmed. If the capacitor is in operational condition but the capacitor temperature is read above 70⁰C then to protect the capacitor, Arduino Mega will order the relay to cut off the flow of electricity to terminal Coil A1 Contactor so that the capacitor is Off (no electric power). At the same time PZEM004T via SCT013 will read electrical parameters such as power factor, current, power, voltage and Kwh. If the power factor reading is <0.8 then to improve the power factor, Arduino Mega will instruct the relay to activate the capacitor but with the condition that the temperature of the capacitor does not exceed 70⁰C. Capacitor temperature readings and electrical parameter readings will be displayed by Arduino Mega to the LCD screen as well as to one of the Internet of Things platforms, namely the Thingspeak application as a monitoring facility. ESP 8266 is a WIFI chip with the TCP/IP Stack protocol that will receive data from Arduino Mega in the form of electrical parameters and temperature of the capacitor and then the data will be sent to the IOT Cloud platform via the internet network using the API KEY (Application Programming Interface) which is the API between interface that can connect one application to another. Data requests by mobile phones and PCs use the IOT (Thingspeak) platform with an API as the link. The results obtained with the design of an internet of things-based capacitor bank monitoring and protection device besides facilitating monitoring in real time easily can also prevent unwanted things such as capacitor explosions.